Influence of hosting a major sports event on patriotic attitudes: The EuroBasket 2013 competition in Slovenia. (May 2019) - Ličen, Simon
Countries with short histories of nationhood often resort to sport to (re-)invent a national identity. This study uses the nationalizing nationalism and social identity frameworks to examine whether hosting a major event such as the European basketball championship for men influenced national identification in Slovenia. Readers of the Slovenian public service website were surveyed at three points in time to determine changes in patriotism, nationalism, internationalism, and smugness in relation to the EuroBasket 2013. Results indicate the almost complete absence of influence on the population as a whole. Nationalistic attitudes did not change after the event based on the respondents' gender and physical activity levels, and only high school graduates displayed an increase in smugness in the week following the competition. Significant differences were found with regard to live and televisual exposure to the event as spectators scored significantly higher on patriotism, nationalism (only TV viewers), and smugness, but not internationalism scales. While hosting this tournament did not contribute to nationalizing nationalism or nation-building, despite the national government's assertion otherwise, even moderate exposure to it fed patriotism. Links between sport events and nationalistic attitudes are discussed in further detail and should inform researchers of sport events and patriotism especially in new democracies.